Earliest evidence of personal ornaments associated with burial: The Conus shells from Border Cave. Issue 93 (April 2016) - d'Errico, Francesco; Backwell, Lucinda
Abstract: The four to six month old infant from Border Cave, found with a perforated Conus shell in a pit excavated in Howiesons Poort (HP) layers dated to 74 ± 4 BP, is considered the oldest instance of modern human burial from Africa, and the earliest example of a deceased human interred with a personal ornament. In this article we present new data retrieved from unpublished archives on the burial excavation, and conduct an in-depth analysis of the Conus found with the infant, and a second similar Conus that probably originates from the same layer. Based on morphological, morphometric and ecological evidence we assign these two shells to Conus ebraeus Linnaeus 1758, a tropical species still living on the nearest coastline to Border Cave, in northern KwaZulu-Natal. This attribution changes the paleoclimatic setting inferred from the previous ascription of these shells to Conus bairstowi, a species endemic to the Eastern Cape and adapted to colder sea surface temperatures. Reconstructions of 74 ka sea surface temperatures along the southern African east coast are consistent with our reassignment. Analysis of shell thanatocoenoses and biocoenosis from the KwaZulu-Natal coast, including microscopic study of their surfaces, reveals that complete, well preserved living or dead Conus, such as those found at Border Cave, are rare on beaches, can be collected at low tide at a depth of c. 0.5–2 m among the rocks, and that the archeological shells were dead when collected. We demonstrate that the perforations at the apex were produced by humans, and that traces of wear due to prolonged utilization as an ornament are present. SEM-EDX analysis of patches of red residue on the Conus found in the pit with the infant indicates that it is composed of iron, phosphorus, silicon, aluminium, and magnesium. Results indicate that, at least in some areas of southern Africa, the use of marine gastropods as ornaments, already attested in Still Bay, extended to the first phases of the HP.